Development of antibody arrays for monoclonal antibody Higher Order Structure analysis - Wang, Xing; Li, Qing; Davies, Michael (Frontiers in Pharmacology, 2013)
Antibody arrays were developed to probe a monoclonal antibody’s three-dimensional structure (3-D structure). Peptides with overlapping regions were designed to cover the whole mAb light chain and heavy chain respectively and used to generate polyclonal antibodies after the conjugation of the peptides to a carrier protein, KLH. It was shown that good peptide specificity was achieved from the antibodies generated. Using more than 30 different polyclonal antibodies to measure the surface epitope distribution, it was shown that the mAb antibody array can detect epitope exposure as low as 0.1% of defined mAb populations. This ELISA-based analysis of mAb epitope exposure can be considered as a measurement of “conformational impurity” in biologics development, similar to the analysis of other product-related impurities such as different forms of glycosylation, deamidation and oxidation. This analysis of “conformational impurity” could provide valuable information on the mAb conformational comparability for biosimilar mAbs as well as novel mAbs, especially in the area of protein immunogenicity. Furthermore, stability studies indicated that there are several conformational “hot spots” in many mAbs tested, especially in the hinge region. This antibody array technology can be used for novel mAb Higher Order Structure (HOS) analysis during process and formulation development. Another important area of application is for biosimilar mAb development where the innovator molecule and biosimilar molecule could be compared based on their systemic “fingerprint” from the 30 plus antibodies.